Abstract - Mardeyanti, Mardeyanti; Yulfitria, Fauziah (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Background:Language ability is indicator for child development and will affect delays or damage to other systems because children's language skills also involve cognitive, motoric, psychological, emotional, and environmental abilities. Right stimulation can improve children's language development. Language stimulation can be done by the mother. Objective: This study aims to determine the effect of maternal stimulation behavior on the language development of pre-school children. Methode: This research is a quantitative research with a cross sectional approach. The population in this study amounted to 50 people with sampling using total sampling technique. Data analysis was processed using chi-square. Results: The results showed the correlation between knowledge and children's language development (p = 0.002), attitude and language development (p = 0.003), behavior (p = 0.005). Conclusion: Based on this analysis, it was found that there is a correlation between mother's knowledge, attitudes and behavior with language development